Toward Scalable Fabrication of Hierarchical Silica Capsules with Integrated Micro‐, Meso‐, and Macropores. Issue 13 (11th February 2016) - Zhou, Weizheng; Tong, Gangsheng; Wang, Dali; Zhu, Bangshang; Ren, Yu; Butler, Michael; Pelan, Eddie; Yan, Deyue; Zhu, Xinyuan; Stoyanov, Simeon D.
Abstract : Hierarchical porous structures are ubiquitous in biological organisms and inorganic systems. Although such structures have been replicated, designed, and fabricated, they are often inferior to naturally occurring analogues. Apart from the complexity and multiple functionalities developed by the biological systems, the controllable and scalable production of hierarchically porous structures and building blocks remains a technological challenge. Herein, a facile and scalable approach is developed to fabricate hierarchical hollow spheres with integrated micro‐, meso‐, and macropores ranging from 1 nm to 100 μm (spanning five orders of magnitude). (Macro)molecules, micro‐rods (which play a key role for the creation of robust capsules), and emulsion droplets have been successfully employed as multiple length scale templates, allowing the creation of hierarchical porous macrospheres. Thanks to their specific mechanical strength, these hierarchical porous spheres could be incorporated and assembled as higher level building blocks in various novel materials. Abstract : Hierachical porous hollow spheres have been successfully created, starting with oil/water or water/oil Pickering emulsions, with integrated micro‐, meso‐, and macropores spanning from 1 nm to 100 μm. Moreover, owing to their well‐ordered poly‐domain shell structures, these large hollow spheres are robust enough to be used as building blocks for creating novel materials.